Competition law and economic inequality - Zac, A (2022)
Scholars and policymakers have recognized inequality as a major social problem affecting political stability, deteriorating public health, and destabilising crime levels. It is increasingly acknowledged in public discourse that competition law could have important effects on inequality levels. However, the specific ways and mechanisms through which a competition law regime might interact with economic inequality remain largely unexplored from an empirical perspective. The thesis aims to address this literature gap.